The impact of parental language ideology and family language policy on language shift and language maintenance: Bilingual perspective - Idaryani Idaryani; Fidyati Fidyati (EduLite: Journal of English Education, Literature and Culture, 2022)
This study aims to investigate parents’ language ideology and family language policy (FLP) among Acehnese families that impact on language shift and language maintenance of Acehnese as a heritage language. The participants of the study were 10 female parents from one of the suburbs in Lhokseumawe City, who have young children from 2 years to 15 years old. The study employed a descriptive qualitative method. The data was collected through semi-structured interviews. The result of the study shows that the majority of parents’ belief that Indonesian is significant for their children's education, has resulted in parents prioritizing Indonesian for their children as the dominant language to speak at home. Furthermore, the family language policy adopted by parents has an impact on language shift among Acehnese children to the Indonesian language.  Parents are reluctant to speak Acehnese to their children as a mother tongue and tend to abandon their heritage language. There are two significant points that are lost due to the consequence of parents’ belief and there the family language policy to choose only Indonesian as a mother tongue to their children; first, it has led their children to grow as monolingual people that somehow is a big loss for the Acehnese children in order to gain various benefits culturally, cognitively, and communicatively from being bilinguals; second, Acehnese is under serious threat as Acehnese children ability in speaking their heritage language keep decreasing. Thus, strong efforts need to be done by all parties for Acehnese language preservation as a part of the unique identity of the Acehnese people.